Calidad de servicio y satisfacción de los usuarios de la Asociación Benéfica PRISMA sede Iquitos 2024 - Güimack Fajardo, Mario (2025)
This thesis aimed to determine the relationship between service quality and user satisfaction at Asociación Benéfica PRISMA – Iquitos site, in 2024. The research was basic, using a quantitative approach, with a descriptive correlational study level, a non-experimental design, and a cross-sectional approach. The sample consisted of 161 users, selected through non probabilistic convenience sampling. A questionnaire was administered using the Likert ordinal scale, using five categories to measure service quality, divided into the dimensions of tangibility, confidence, responsiveness, safety, and empathy, and user satisfaction, through the dimensions of expectations, perceived quality, general satisfaction index, complaints, and loyalty. The descriptive results showed a generalized positive perception of 100% regarding service quality and 98.14% in user satisfaction. In inferential statistics, a Spearman Rho coefficient of 0.663 was obtained with a p-value<0.05 between service quality and user satisfaction, which indicates a moderate and significant positive correlation. Positive and significant correlations were found between all dimensions of service quality and user satisfaction, with safety being the dimension with the highest correlation with a Spearman Rho of 0.740 with a p-value <0.05, and responsiveness being the least influential with a Spearman Rho of 0.394 with a p-value <0.05. It is concluded that there is a significant relationship between service quality and user satisfaction at Asociación Benéfica PRISMA - Iquitos site in 2024.